THE IMPORTANCE AND FEATURES OF REHABILITATION AFTER ABDOMINAL SURGERY (Proceedings of International Educators Conference, 2024)
The article discusses the relevance and importance of rehabilitation after abdominal surgery. Modern recovery methods such as early activation, diet therapy, physiotherapy treatments, and psychological support were analyzed. The basis for the study was data from scientific sources and databases Google Scholar, Scopus and PubMed. The results of the analysis show that early and comprehensive rehabilitation reduces the risk of complications and accelerates the recovery process of patients. The results highlight the need to further improve rehabilitation programs to improve patients' quality of life in the postoperative period.